Spectrum of pigmented lesions of skin: a retrospective study in a tertiary health care of Southern Assam - Ahmed, S. K. Abdullah; Ullah, Sania Sultana; Bhuyan, Karishma; Deka, Monoj K.; Sheikh, Shah Alam (International Journal of Research in Medical Sciences, 2021)
Background: Pigmented lesions are one of the most common cause for dermatological consultation. Most of them are benign, while a majority of them have malignant transformation and are called as melanoma. A careful histopathological interpretation by the pathologist is needed in the diagnosis and management of these lesions. Aims and objectives of the study were- 1. To study the spectrum of various pigmented skin lesions. 2. To establish the correlation between the microscopic pathological findings of various skin lesions with the presenting clinical features. Methods: A 3-year study was conducted in the pathology department of tertiary care centre on all skin biopsy tissue which came as pigmented lesion. The entire skin biopsy is submitted for routine processing and embedded in paraffin wax. 3-5 mm thick paraffin sections of the skin biopsy are stained with H and E. Results: Out of 432 skin biopsies studied during this period, 58 cases were diagnosed as pigmented skin lesions. Of these, the biopsy tissue was inadequate in 5 cases while five cases presented with non-specific findings. Of the remaining cases, 15 were malignant and 33 were benign lesions. Only 18 of these were of melanocytic origin with 8 cases of malignant melanoma and 10 nevi. In the present study an analysis of the clinical diagnosis with the histopathological diagnosis revealed a positive correlation in 54% cases. Conclusions: A good clinical correlation and biopsy with histopathological diagnosis is necessary for the accurate diagnosis and definite treatment of patients with pigmented skin lesions.